The Role of Pometone (Pomegranate seed oil) in Ameliorating the Deleterious Effect of Methionine Overload on Some Histological Aspects of heart and aorta in Female Rabbits (Part-II): Baraa Najim Al-Okaily@ and Lekaa Najim Abdulla - Al-Okaily, Baraa Najim (The Iraqi Journal of Veterinary Medicine, 2014)
This experiment was aimed to investigate the role of pomegranate seed oil (PSO) in ameliorating the deleterious effects of methionine overload on some histopathological structure of heart and aorta in adult female rabbits. Thirty-Two female rabbits divided into four groups eight animals each, and treated for 42 days daily as follows: the first groups were drenched drinking corn oil, serving as control (group C), second group (group T1) were intubated orally with methionine 100mg/kg. B.W, while the third group (groupT2) were intubated orally with methionine 100mg/kg. B.W and pomegranate seed oil (PSO) 30 mg /Kg. B.W, and the animals in group T3 were intubated orally with pomegranate seed oil 30 mg /Kg. B.W. At the end of the experiment rabbits were sacrificed. Serial sections from the heart and aorta were prepared and examined microscopically. Histological examination of heart and aorta of methionine overload treated group (T1) showed edema ,RBCs and few neutrophils infiltration ,with vacuolar degeneration of cardiac muscle cells , fragment of muscle fiber, congested blood vessels between muscle fibers. An increase in thickness of intima, erosion and mononuclear cells infiltration in sub intima of aorta were also observed. Histological sections of heart and aorta in T2 and T3 groups showed the absence of histopathological lesions in aortic tissue with moderate edema between muscle fiber of T2 group as comparing to group T1. In conclusion, the results confirm the cardioprotective role of pomegranate seed oil by ameliorating the effect of methionine overload on cardiac muscle and aorta.